THE RIVALRY OF THE TWO GREAT POWERS: IS IT A REGIONAL SECURITY THREAT? - Sumadinata, Widya Setiabudi (Sean Institute, 2022)
As a result of the country's economic and military resurgence, China has become one of the primary actors in the effort to maintain stability in the Asia Pacific region. As a result of the United States' observation of this phenomenon, the nation's foreign policy shifted its focus from the Atlantic region to the Pacific region. The competition between the two great powers will have an effect on the safety of the surrounding area. As a result, the purpose of this paper is to attempt to discuss the security dynamics of the Asia Pacific region against the backdrop of the competition between the world's two most powerful superpowers, the United States and China. A qualitative approach, a method that involves reviewing previous research, and descriptive analysis were utilized in this study. The conversation will start with an analysis of the relationship between the two major powers in the region, followed by the creation of a picture depicting US dominance as the main power in Asia Pacific, which is rivaled by China through the development of military strength, and an examination of US defense policy and China's military development as a form of balance of power in the Asia Pacific region.